Банкротство мнимых ценностей: [роман] / Олег Рой - Рой Олег (Капризы судьбы, 2012)
Экземпляры: 7 (20200210) / Инвентарный номер: 64392 / Цена: 120.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 58 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6